Presumptive complicating Clostridium paraputrificum bacteremia as a presenting manifestation in a patient with undiagnosed ulcerative colitis followed by acute colonic pseudo-obstruction. (2023) - Kaneko, Masahiko; Moriyama, Chie; Masuda, Yuya; Sawachika, Hiroshi; Shikata, Hisaharu; Matsukage, Shoichi
Abstract: Clostridium paraputrificum is a member of the commensal flora of the gastrointestinal tract and skin. Despite being linked with cases of severe invasive infection, this organism is an uncommon pathogen in humans. Here, we report a case of undiagnosed ulcerative colitis in which the presentation was one of presumptive complicating C. paraputrificum bacteremia and, later, acute colonic pseudo-obstruction. The patient was an elderly male with prostate cancer who was admitted in a state of shock secondary to suspected septicemia from an abdominal source. Only one of two sets of anaerobic blood cultures were positive for C. paraputrificum . Endoscopic and pathological investigations revealed proctitis consistent with ulcerative colitis. The patient's abdominal manifestations worsened, and abdominal imaging demonstrated de novo massive colonic dilatation without any apparent mechanical obstruction. We speculated that C. paraputrificum bacteremia caused by undiagnosed ulcerative colitis had created ideal conditions for acute colonic pseudo-obstruction. This case demonstrates that C. paraputrificum bacteremia can be associated with latent severe gastrointestinal pathologies, indicating the need to investigate any abdominal source of infection, even if only a single blood culture is positive.